Resposta da cultura do feijão (Phaseolus vulgaris L.) `à adubação nitrogenada e fosfatada - Berger, Paulo Geraldo; Berger, Paulo Geraldo; Vieira, Clibas; Chagas, José Mauro; Braga, José Mário; Cardoso, Antônio Américo (Revista Ceres, 2025)
In order to determine the effect of N and P fertilization on beans (Phaseolus vulgaris L. cv. ‘Negrito 897), a factorial 5 X 5 experiment was carried out, during the «rainy» season, at Coimbra, State of Minas Gerais. The applied levels of N and P05 were 0, 30, 60, 90, and 120 kg/ha, as ammonium sulfate, and 0, 60, 120, 180, and 240 kg/ha, as ordinary superphosphate, respectively.